By His Excellency Jonathan Trumbull, Esquire, governor and commander in chief, in and over the state of Connecticut. A proclamation : ... Thursday the twenty-eighth day of November next, to be observed as a day of public thanksgiving ... Given under my hand, at New-Haven, this 21st day of October ... one thousand seven hundred and ninety-nine . (Printed by Thomas Green and Son, 1799)
October 21, 1799 broadside issued by Governor Jonathan Trumbull of Connecticut, proclaiming November 28th as a day of thanksgiving for all God' goodness and loving kindness.